Analysis of Website-Based Information Tecgnology System on Patient Service Quality at Murni Murni Teguh Medan Hospital - Fernando; Pesta Gultom; Muhammad Ali Akbar (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study aims to determine whether the Website-Based Information Technology System and E-Complaint have a significant effect on Service Quality at the Murni Teguh Medan Hospital. This study uses quantitative data methods and the data source is primary data. The population in this study were patients at the Murni Teguh Medan Hospital totaling 53,800 patients. The sample of this study were patients of the Teguh Medan Pure Hospital totaling 100 respondents using purposive sampling data collection techniques. Data analysis and testing consists of validity test, reliability test, descriptive statistical test, classical assumption test, multiple regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and determination coefficient test. The results showed that the Website-Based Information Technology System had a partially significant effect on Service Quality with a t value of 13.515> t table 1.66055. E-Complaint has a partially significant effect on Service Quality with a t value of 4.599> t table 1.66055. Website-Based Information Technology Systems and E-Complaint simultaneously have a significant effect on Service Quality with a calculated F value of 100,129> F table 2.36 with a regression coefficient value of 67.4%.